Benturan Ideologis dalam Novel Perempuan Bersampur Merah Karya Intan Andaru - Deki Sulistiyo; Apsanti Djokosuyatno; Oom Rohmah Syamsudin (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2022)
The research aims to analyze the ideological clash in the Perempuan Bersampur Merah novel created by Intan Andaru through characters and sacrifices and background. The research Approach use qualitative approach to describe shape, impact, and exploitation ideology through figures and characterization in social group. The research method is used bibliography method. To analyze novel’s elements Intrinsic use Charles Morris semiotic structure approach, An Analysis Discourse Critical model Norman Fairclough is used to analyze novel’s elements extrinsic. Based on the research results, The flow of Perempuan Bersampur Merah novel was jumping not sequentially with chronological event. Plot framed with event from the past. Character main is Sari. Theme is about human feeling. Room and Time relate with events in Banyuwangi in 1998. The ideology formation of novel is depicted by Intan Andaru as following : The ideology of society group that against culture infatuation that links with witchcraft clash with The ideology group people who think witchcraft and infatuated is culture that must be preserved, Next The of group apparatus and party weak security that should be give protection clash with the ideology of group vigilante society group oppressive dominant witch doctor with the stigma of a shaman witchcraft clash with group helpful shaman treatment Then ideology of equality and Justice voice group clash with ideology of group people who are trying cover events ever was happen. Keywords: Analysis Discourse Critical, Ideological clash, Perempuan Bersampur Merah novel.